Knowledge And Adolescent Attitudes In Urban About Hiv And Aids - Irmawati; Andi Suswani; Amirullah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2019)
The phenomenon that is happening now is that many teenagers do not know the impact of HIV and AIDS both in terms of knowledge and from the attitudes of teenagers themselves. So that the research emphasizes more on the knowledge and attitudes of adolescents about HIV and AIDS. This study aims to identify the knowledge and attitudes of high school adolescents in urban areas about HIV and AIDS in Mas Ma’arif Bulukumba, Bulukumba District. Measurement in this study is the Analitik Descriptive study which is a form of research that is conducted with a survey approach. The sample was 36 respondents. Sampling is done using total sampling. Based on the results of the research that has been done, out of 36 respondents about the level of students' knowledge of HIV and AIDS, the highest number of respondents was high knowledge, namely 24 students (66.7%), then low knowledge by 12 students (33.3%). And those who have attitudes about HIV and AIDS with the highest number of respondents are good attitudes, namely 30 students (83.3%) then bad attitudes as many as 6 students (16.7%). Based on the results of research on students' knowledge and attitudes about HIV and AIDS MAS Ma'arif Bulukumba has good knowledge and attitudes because of the large amount of information obtained by students so that students get an understanding of HIV and AIDS.